(untitled) (Research, Society and Development, 2020)
Currently, Brazil has more than 700 thousand people in prisons. In this regard, it is clear that the AIDS epidemic in Brazilian prisons is a major public health problem. In this perspective, among the aggravating and proliferating factors of the disease, the overcrowding of prisons, unprotected sexual practices and the unhealthiness of cells stand out. In this study, the Bireme, Scielo, Pubmed and Google Scholar research bases were used, and the descriptors used were: “health care”, “HIV (acquired immunodeficiency syndrome)” and “prisoners and prisons”. The objective is to answer the question: "How does the doctor-patient relationship take place in the care provided to people with HIV in the prison system?". The implementation of the National Policy for Comprehensive Health Care for Persons Deprived of Liberty in the Prison System (PNAISP) was also analyzed, which presumes comprehensive, continuous and resolutive assistance with control and reduction of injuries to prison health demands. As for the doctor-patient relationship, there are difficulties in care, due to the permanence of the stigma related to HIV / AIDS and the retrograde prevalence of the use of the biomedical model, known for focusing only on the disease, by health professionals, such adversities decrease both adherence and treatment effectiveness. Therefore, a more humanistic and welcoming doctor-patient relationship on the part of the health professional is of utmost importance, thus having greater chances of success in therapy and in the interpersonal relationship with the sick.